Developing encyclopedia book of traditional games in Gresik City on learning my cultural theme in kindergarten - Nenny Chanidatus Shofiyah; Kartika Rinakit Adhe; Eka Cahya Maulidiyah; Nurhenti Dorlina Simatupang (Universitas Ahmad Dahlan, 2022)
Grass motor skill and culture knowledge is important for early childhood development, however in the North Gresik Region found that children have never been introduced to local culture, lack of games variety, and there is no development of books that can support children's knowledge of children's culture and gross motor skills. So that, this study aims to develop an encyclopedia of traditional games. This development research uses the ADDIE model with involved PGRI Dalegan and Muslimat NU 41 Kindergarten (n=30) which are divided into two classes. Data collected using questionnaires and observation. This research produces a product in the form of a traditional game encyclopedia of Gresik City which is feasible and effective to be applied to the learning of my culture theme with a material validation percentage value of 95.83%, media validation of 88.63% which is classified as very good category. Data analysis used independent sample t-test with the value of = 0.000 that there was a difference in gross motor skills between the experimental class and the control class. The results obtained after applying the traditional game encyclopedia of Gresik city, children can understand and carry out activities playing various traditional games of Gresik city. This book is useful for improving children's gross motor skills and introducing local culture to early childhood, especially traditional games